Recent Advances of Cell Membrane‐Coated Nanomaterials for Biomedical Applications - Liu, Wen‐Long; Zou, Mei‐Zhen; Qin, Si‐Yong; Cheng, Yin‐Jia; Ma, Yi‐Han; Sun, Yun‐Xia; Zhang, Xian‐Zheng (Advanced functional materials, 2020)
Surface modification of nanomaterials is essential for their biomedical applications owing to their passive immune clearance and damage to reticuloendothelial systems. Recently, a cell membrane‐coating technology has been proposed as an ideal approach to modify nanomaterials owing to its facile functionalized process and good biocompatibility for improving performances of synthetic nanomaterials. Here, recent advances of cell membrane‐coated nanomaterials are reviewed based on the main biological functions of the cell membrane in living cells. An overview of the cell membrane is introduced to understand its functions and potential applications. Then, the applications of cell membrane‐coated nanomaterials based on the functions of the cell membrane are summarized, including physical barrier with selective permeability and cellular communication via information transmission and reception processes. Finally, perspectives of biomedical applications and challenges about cell membrane‐coated nanomaterials are discussed. Recent advances of cell membrane‐coated nanomaterials are summarized here based on the main biological functions of the cell membrane, including physical barrier and cellular communication. Perspectives of biomedical applications and challenges of cell membrane‐coated nanomaterials are also discussed.